2005
DOI: 10.1021/ja051508a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Cycling of Niobium and Vanadium Catalyzed Nanostructured Magnesium

Abstract: The reaction of hydrogen gas with magnesium metal, which is important for hydrogen storage purposes, is enhanced significantly by the addition of catalysts such as Nb and V and by using nanostructured powders. In situ neutron diffraction on MgNb(0.05) and MgV(0.05) powders give a detailed insight on the magnesium and catalyst phases that exist during the various stages of hydrogen cycling. During the early stage of hydriding (and deuteriding), a MgH(1< x < 2) phase is observed, which does not occur in bulk MgH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(196 citation statements)
references
References 33 publications
10
181
1
2
Order By: Relevance
“…The crystal structure of magnesium is hexagonal close packing and the calculated Mg bulk lattice constants are a Mg = b Mg = 3.190Å with the c/a value of 1.623, which are in good agreement with the experimental values 48,49 and previous theoretical results. [50][51][52] Magnesium hydride, whose crystal structure is simple tetragonal, is a highly stable hydride with strong Mg-H bond, which is a mixture of ionic and covalent bonding.…”
Section: A the Bulk Properties Of Magnesium And Magnesium Hydridesupporting
confidence: 88%
“…The crystal structure of magnesium is hexagonal close packing and the calculated Mg bulk lattice constants are a Mg = b Mg = 3.190Å with the c/a value of 1.623, which are in good agreement with the experimental values 48,49 and previous theoretical results. [50][51][52] Magnesium hydride, whose crystal structure is simple tetragonal, is a highly stable hydride with strong Mg-H bond, which is a mixture of ionic and covalent bonding.…”
Section: A the Bulk Properties Of Magnesium And Magnesium Hydridesupporting
confidence: 88%
“…6 On the other hand, Mg−Nb−O perovskite phase was also found in the dehydrogenated composite and believed to help with hydrogen transportation. 7 Transition-metal oxides also show the catalytic effect on facilitating hydrogen absorption and desorption in nanostructured MgH 2 . 8−13 Among those catalysts studied so far, Nb 2 O 5 showed a superior catalytic effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The latter can be substantially increased using small grain sizes 1 and adding transition metals or their oxides. In particular, niobium 2 and palladium 3,4 have a pronounced impact on the sorption kinetics. Previous studies [4][5][6] showed that spark discharge generation (SDG) is a versatile method for the production of metal nanoparticles.…”
mentioning
confidence: 99%